2018
DOI: 10.1021/acsomega.7b02002
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and Secondary Ozonide of the Criegee Intermediate of Sabinene

Abstract: A computational study of the formation of secondary ozonide (SOZ) from the Criegee intermediates (CIs) of sabinene, including hydration reactions with H 2 O and 2H 2 O, was performed. All of the geometries were optimized at the B3LYP and M06-2X with several basis sets. Further single-point energy calculation at the CCSD(T) was performed. Two major pathways of SOZ formation suggest that it is mainly formed from the sabinene CI and formaldehyde rather than sabina ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…35 Specifically, Heine et al 36 and Fooshee et al 37 show SOZs from squalene particles and surfaces, respectively, and other sources include ascorbic acid (Enami et al) 38 and sabinene (Almatarneh et al). 39 In addition, as illustrated by multiphase ozonolysis studies of oleic acid and squalene, products with other functional groups including aldehydes and carboxylic acids are also identified. 35,36 Multiple studies have demonstrated that ozonolysis of oleic acid is relatively efficient, with an ozone uptake coefficient (γ) on the order of 10 −3 , 40−44 whereas squalene has a γ on the order of 10 −4 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Specifically, Heine et al 36 and Fooshee et al 37 show SOZs from squalene particles and surfaces, respectively, and other sources include ascorbic acid (Enami et al) 38 and sabinene (Almatarneh et al). 39 In addition, as illustrated by multiphase ozonolysis studies of oleic acid and squalene, products with other functional groups including aldehydes and carboxylic acids are also identified. 35,36 Multiple studies have demonstrated that ozonolysis of oleic acid is relatively efficient, with an ozone uptake coefficient (γ) on the order of 10 −3 , 40−44 whereas squalene has a γ on the order of 10 −4 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…The formation of SOZs not only arises from triglycerides but also via ozonolysis of numerous unsaturated compounds . Specifically, Heine et al and Fooshee et al show SOZs from squalene particles and surfaces, respectively, and other sources include ascorbic acid (Enami et al) and sabinene (Almatarneh et al) . In addition, as illustrated by multiphase ozonolysis studies of oleic acid and squalene, products with other functional groups including aldehydes and carboxylic acids are also identified. , Multiple studies have demonstrated that ozonolysis of oleic acid is relatively efficient, with an ozone uptake coefficient (γ) on the order of 10 –3 , whereas squalene has a γ on the order of 10 –4 . , These reactions proceed through the formation of the unstable primary ozonide, which falls apart into biradical Criegee intermediates (CI) and aldehydes with a number of subsequent reactions, ,, ,, as described later in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical work by Jørgensen and Gross afforded an insight into the experimental work of Naa and co-workers by surveying plausible, pertinent reaction mechanisms [18]. Moreover, our previous work on ozonolysis reactions provided good initial guesses that helped us attain a complete picture about the proposed mechanisms for this study [7,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 90%
“…The quantum calculations using density functional theory (DFT) and composite methods were performed utilizing the Gaussian 09 package . The rate constant of the ozonolysis reaction and it is resulting reactions has been computed using transition state theory (TST) at 298.15 K. The selection of methods and basis sets is based on our previous work on the atmospheric ozonolysis reaction mechanisms of sabinene and phenanthrene . The stationary and saddle points were optimized using the B3LYP method with the split‐valence polarized 6‐31G(d,p) basis set.…”
Section: Methodsmentioning
confidence: 99%